Sintering method

CN122996488APending Publication Date: 2026-10-27CELANESE MERCURY HOLDINGS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480087617.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-14
Filing Date
2024-12-10
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,用于将电子部件烧结在一起的工艺需要在高工艺温度下烧结并且利用管芯键合装备来对烧结布置加压,这增加了制造时间、复杂性和成本

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996488A_ABST
    Figure CN122996488A_ABST
Patent Text Reader

Abstract

A sintering method for joining at least two components is provided. The method includes disposing an electrically conductive paste on a first component. The electrically conductive paste includes a metal powder dispersed in an organic vehicle. The metal powder has a D50 ranging from about 200 nm to about 500 nm. The method includes drying the electrically conductive paste to form a dried electrically conductive paste, and disposing a second component on the dried electrically conductive paste to form a component arrangement. The method includes sintering the component arrangement without applying an external pressure to the component arrangement. Electronic articles are also provided.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related applications

[0002] This application is based on and claims priority to U.S. Provisional Patent Application Serial No. 63 / 609,899, filed on December 14, 2023, which is incorporated herein by reference. Background Technology

[0003] Solder bonding, or sintering, is used to bond electronic components to a substrate. Sintered bonding provides sintered bonding between components with high temperature resistance, while ensuring good electrical and thermal contact. However, the process for sintering electronic components together requires sintering at high process temperatures and using die bonding equipment to pressurize the sintered arrangement, which increases manufacturing time, complexity, and cost. Furthermore, sintering processes that do not utilize pressure require long sintering times, and it can be very difficult to control the fillet thickness during sintering.

[0004] With this in mind, there is a need for improved conductive sintering materials and methods for sintering at lower temperatures and pressures. Summary of the Invention

[0005] According to one embodiment of this disclosure, a sintering method for bonding at least two components is provided. The method includes disposing a conductive paste on a first component. The conductive paste comprises metal powder dispersed in an organic medium. The metal powder has a D50 ranging from about 200 nm to about 500 nm. The method includes drying the conductive paste to form a dried conductive paste; disposing a second component on the dried conductive paste to form a component arrangement; and sintering the component arrangement without applying external pressure to the component arrangement.

[0006] According to other embodiments, an electronic article is provided, comprising a semiconductor chip sintered to a substrate with a conductive paste. The conductive paste comprises metal powder dispersed in an organic medium. The metal powder has a D50 ranging from about 200 nm to about 500 nm.

[0007] Other features and aspects of this disclosure are set forth in more detail below. Attached Figure Description

[0008] The full and illustrative disclosure of this disclosure, including its best mode, which will be readily apparent to those skilled in the art, is set forth in more detail in the remainder of the specification, with reference to the accompanying drawings, in which: Figure 1 This is a schematic diagram of an example method for arranging forming components according to one embodiment of the present disclosure; and Figure 2 This is a flowchart of an example method for arranging components according to one embodiment of the present disclosure.

[0009] Reference numerals used repeatedly in this specification and drawings are intended to indicate the same or similar features or elements of this disclosure. Detailed Implementation

[0010] Those skilled in the art will understand that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of this disclosure.

[0011] Generally, this disclosure relates to a sintering method for joining at least two components. The method includes applying a conductive paste to a first component. The conductive paste comprises metal particles dispersed in a solvent. The conductive paste may also comprise a polymer. The conductive paste is dried, and after drying, a second component is placed on the dried conductive paste. During sintering, the component arrangement is sintered without the application of external pressure.

[0012] Advantageously, by selectively controlling the specific concentrations of the components in the conductive paste, the inventors have discovered that the resulting conductive paste can provide effective sintered bonding between parts, even during sintering at 0 MPa. Furthermore, the conductive paste of this disclosure reduces the need for pressure application during the sintering process and also provides a reduced sintering time. Therefore, manufacturing complexity is reduced, and increased processing speeds are achieved. Additionally, the method provided herein reduces the generation of fillets during sintering, which reduces electrical short circuits between sintered parts.

[0013] The various embodiments of this disclosure will now be described in more detail.

[0014] I. Conductive paste

[0015] a. Conductive materials

[0016] As described above, conductive pastes include conductive materials. There are no particular limitations on the conductive materials used in this disclosure, as long as they do not adversely affect the technical effects of this disclosure. Conductive materials may include those having a conductivity of approximately 7.00 × 10⁻⁶ at 293 Kelvin in the embodiments. 6 Siemens (S) / m or higher, and in another embodiment, approximately 8.50 × 10⁻⁶ at 293 Kelvin. 6 S / m or higher, and in another embodiment approximately 1.00 × 10⁻⁶ at 293 Kelvin. 7 S / m or higher, or in another embodiment approximately 4.00 × 10⁻⁶ at 293 Kelvin. 7 Conductive materials with a conductivity of S / m or higher. The conductive material can be a metal powder selected from the group consisting of: aluminum (Al, 3.64 × 10⁻⁶). 7 S / m), nickel (Ni, 1.45×107 S / m), copper (Cu, 5.81×10 7 S / m), silver (Ag, 6.17×10 7 S / m), gold (Au, 4.17×10 7 S / m), molybdenum (Mo, 2.10×10 7 S / m), magnesium (Mg, 2.30×10 7 S / m), tungsten (W, 1.82×10 7 S / m), cobalt (Co, 1.46×10 7 S / m), Zinc (Zn, 1.64×10 7 S / m), Platinum (Pt, 9.43×10 6 S / m), palladium (Pd, 9.5×10 6 S / m), its alloys and their mixtures.

[0017] In the implementation scheme, the conductive material may be silver. When silver is used as the conductive material, it may be in the form of metallic silver, silver derivatives, and / or mixtures thereof. Examples of silver derivatives include silver oxide (Ag₂O), silver salts (such as silver chloride (AgCl), silver nitrate (AgNO₃), silver acetate (AgOOCCH₃), silver trifluoroacetate (AgOOCCF₃), or silver phosphate (Ag₃PO₄), silver-plated composite materials or silver-based alloys with a silver coating on their surface, etc.

[0018] Conductive materials can be in the form of metal powder containing metal particles of various shapes (e.g., spherical, flake, irregular, and / or mixtures thereof). In some embodiments, the metal powder includes spherical particles. For example, in one embodiment, at least about 60% to about 100%, such as about 70% to about 90%, such as about 85% to about 100%, of the metal particles are in the form of spherical particles.

[0019] In one embodiment, the particle size (D50) of the metal powder can be from about 200 nm to about 3500 nm, such as from about 250 nm to about 1000 nm, such as from about 300 nm to about 900 nm, such as from about 450 nm to about 850 nm. Specifically, the particle size (D50) of the metal powder can be from about 200 nm to about 500 nm, such as from about 250 nm to about 450 nm, such as from about 300 nm to about 400 nm, such as from about 210 nm to about 360 nm. The particle size (D50) can be determined by laser diffraction scattering. For example, in an embodiment, the particle size (D50) can be measured by laser diffraction scattering using a Macchiato model S-3500. Other instruments known for measuring particle size (D50) can also be used without departing from the scope of this disclosure. A mixture of metals with different average particle size, particle size distribution, or shape can also be used. As used herein, “D50” means that 50% of the particles are smaller than the stated size, and also means that 50% of the particles are larger than the stated size. The metal powder may have a D10 ranging from about 100 nm to about 1,000 nm, such as about 150 nm to about 500 nm, such as about 150 nm to about 350 nm. In embodiments, the metal powder has a D10 ranging from about 150 nm to about 300 nm, such as about 170 nm to about 280 nm, such as about 190 nm to about 260 nm, such as about 210 nm to about 240 nm, such as about 160 nm to about 240 nm. As used herein, “D10” means that 10% of the particles in the powder are smaller than the stated size. Furthermore, the metal powder may have a D90 ranging from about 200 nm to about 2,000 nm, such as about 350 nm to about 1,000 nm, such as about 400 nm to about 750 nm. In an embodiment, the metal powder has a D90 ranging from about 250 to about 930, such as about 300 nm to about 900 nm, such as about 350 nm to about 850 nm, such as about 400 nm to about 800 nm, such as about 450 nm to about 750 nm, such as about 500 nm to about 700 nm, such as about 270 nm to about 570 nm. As used herein, “D90” means that 90% of the particles in the powder are smaller than the stated size.

[0020] In one embodiment, the specific surface area (SA) of the metal powder can be approximately 0.5 m². 2 / g to approximately 5m 2 / g, in another embodiment, is approximately 1m 2 / g to approximately 3.5m 2 / g, and in another embodiment approximately 1.5m 2 / g to approximately 2.5m 2 / g. In the embodiment, the metal powder has a density of approximately 0.9m. 2 / g to approximately 4m 2 / g, such as about 1m 2 / g to approximately 3m 2 / g, such as approximately 2.8m 2 / g to approximately 3.8m 2 / g SA. Specific surface area can be determined by the BET method using Quantachrome Instruments Corporation's Monosorb. ™ Measurement.

[0021] In one embodiment of this disclosure, the metal powder is present in an amount of about 50% to about 98% by weight of the conductive paste, such as about 70% to about 95% by weight, such as about 75% to about 85% by weight, such as about 85% to about 98% by weight, such as about 85% to about 91% by weight.

[0022] The metal particles in the powder can be coated with any suitable surfactant. In one embodiment, the metal particles are coated with lipids, such as fatty acids. Fatty acids may include free fatty acids, fatty acid salts, or fatty acid esters, which may be branched, unbranched, saturated, or unsaturated. Suitable fatty acids include, but are not limited to, oleic acid, stearic acid, lauric acid, caprylic acid, capric acid, myristic acid, palmitic acid, arachidic acid, benzyl acid, tetracosanoic acid, ceric acid, and combinations thereof. In other embodiments, the metal particles may be coated with anionic surfactants. Suitable anionic surfactants include sodium lauryl sulfate, sodium lauryl polyoxyethylene ether sulfate, ammonium lauryl sulfate, sodium lauryl polyoxyethylene ether sulfate, sodium stearate, potassium cocoate, and combinations thereof. The coatings disclosed herein can be applied to the surface of the metal particles in any manner known in the art.

[0023] In the implementation, the conductive material is lead-free and does not contain lead or lead components. Specifically, the conductive material is substantially free of lead and its derivatives (e.g., lead oxides, such as lead monoxide (PbO), lead dioxide (PbO2), or lead tetroxide (Pb3O4)).

[0024] Metal powder can have a density of approximately 1 g / cm³. 3 Approximately 7g / cm 3 Such as approximately 2g / cm 3 Approximately 5g / cm 3 Such as approximately 3g / cm 3 Approximately 4g / cm 3 The tap density. The tap density can be determined according to ISO 3953:2011.

[0025] In the implementation scheme, the conductive material may include commercially available silver powder, including CR801-DF, CR801DF-045HM, CR801DF-045W, CR801-DF-045WN, CR805-045, CR901DF-03, S1804W, S18040-NM2, SF134, and SF160 available from Ames Goldsmith Corporation; DJA03N available from Toyo Chemical Co., LTD.; EA-0101, P500-1, P500-13, P543-80, P543-91, P903-2, P903-3, and P98-40 available from Metalor Technologies; P3072FX091 and P3072 GVP097 available from DEMI Specialty Chemicals & Co.; and silver powder available from Osaka Soda Co., The KSN-114 TypeDP200, KSN-200Type DP200, and KSN-200 TypeDP500 were acquired by LTD.

[0026] b. Organic mediator

[0027] Conductive pastes may include organic mediators. For example, conductive materials may be mixed with organic mediators to form conductive pastes. Organic mediators may be in liquid or viscous form to facilitate mixing. Suitable organic mediators allow the conductive material to be uniformly dispersed therein and have appropriate viscosity to deliver the conductive material to the surface of the article, such as by screen printing, stencil printing, etc. The conductive pastes provided also offer good drying rates and excellent sintering properties, even when sintering is performed without external pressure during sintering.

[0028] Organic mediators may include organic polymers and solvents. In other embodiments, organic mediators may include only solvents and exclude organic polymers. Various inert adhesive materials may be used as organic polymers. Organic polymers may be cellulose derivatives (e.g., ethyl cellulose, methyl cellulose, ethyl hydroxyethyl cellulose, etc.); phenolic resins; acrylate polymers (e.g., polymethyl methacrylate, polymethyl methacrylate of lower alcohols); rosin; acetate derivatives (e.g., monobutyl ether of ethylene glycol monoacetate); glycol derivatives (e.g., polyethylene glycol); and mixtures thereof. Organic polymers may be present in amounts from about 0.1% by weight to about 1.2% by weight, such as from about 0.6% by weight to about 1% by weight, such as from about 0.8% by weight to about 1% by weight, based on the total weight of the conductive paste.

[0029] Solvents may include alcohols (e.g., dodecanol, ester alcohol, terpineol); esters (e.g., benzoate esters, such as dibutyl phthalate, diester esters); diols (e.g., butyl carbitol, dibutyl carbitol, butyl carbitol acetate, hexanediol); hydrocarbons or mixtures of hydrocarbons (e.g., kerosene); and mixtures thereof. The choice of solvent should take into account the solubility of the organic polymer. The solvent may be present in amounts from about 1% to about 20% by weight, such as from about 3% to about 18% by weight, such as from about 6% to about 15% by weight, such as from about 8% to about 12% by weight, based on the total weight of the conductive paste.

[0030] The organic medium may optionally include organic additives. Organic additives may be one or more of thickeners, stabilizers, viscosity modifiers, surfactants, wetting agents, thixotropic agents, and other conventional additives (e.g., colorants, preservatives, or oxidants). The amount of organic additive depends on the desired properties of the resulting conductive paste. The selection of additives is not limited, as long as they do not adversely affect the technical effects of this disclosure.

[0031] II. Products

[0032] Conductive paste can be applied to one or more components, dried, and used to sinter at least two components together. Specifically, the conductive paste of this disclosure can be applied to a first component, dried, and then a second component can be disposed on the dried conductive paste to form a component arrangement. The dried conductive paste can then be sintered to form a sintered bond between the first and second components. The conductive paste can be used in a variety of applications (e.g., power electronic devices, etc.) where electrical connections with excellent adhesion are required, as further described and illustrated in the examples provided below. The component arrangement may include electronic articles, thereby forming a sintered bond between a semiconductor chip and a substrate via the conductive paste described herein.

[0033] Conductive pastes can be used to provide sintered connections between components. For example, such as... Figure 1As shown, conductive paste 10 is disposed on substrate 12 (e.g., a first component). The substrate material may include any conductive, dielectric, or insulating material. Suitable substrates include printed circuit boards. Conductive paste 10 contains a solvent and is considered to be wetting. Conductive paste 10 may be disposed on substrate 12 by any suitable method, including screen printing, stencil printing, dispensing printing, or jet printing. At 20, conductive paste 10 is dried, thereby forming a dried conductive paste 14 on substrate 12. At 30, a second component 16 is disposed on the dried conductive paste 14. The second component 16 may include a semiconductor chip or other suitable electronic component. At 40, substrate 12, dried conductive paste 14, and second component 16 form a sinterable component arrangement 17. Notably, component arrangement 17 can be sintered without applying additional external pressure to component arrangement 17. For example, in an embodiment, component arrangement 17 may be sintered at a sintering pressure of 0 MPa. Furthermore, in the embodiments, the component arrangement can be sintered without the use of a die or other equipment, and can alternatively be sintered in any suitable furnace capable of reaching the desired sintering temperature. Additionally, the component arrangement 17 can be sintered at sintering temperatures ranging from about 200°C to about 350°C, such as about 200°C to about 280°C, such as about 220°C to about 280°C, such as about 250°C to about 300°C, such as about 270°C to about 290°C.

[0034] In addition, such as Figure 1 As depicted, component assembly 17 may include rounded corners 18 formed by conductive paste 10. Rounded corners 18 are typically formed on one or more sidewalls 15 of the second component 16 (e.g., a semiconductor chip). Rounded corners 18 may have a height H, generally vertical, relative to the sidewall 15, less than 30 µm, such as less than 20 µm, such as less than about 10 µm. For example, in embodiments, component assembly includes rounded corners with heights from about 1 µm to about 30 µm, such as from about 5 µm to about 25 µm, such as from about 10 µm to about 20 µm. For example, the inventors have found that using the conductive paste of this disclosure produces rounded corners with shorter heights compared to other wet pastes or wet processes that have observed rounded corners with heights much greater than 30 µm.

[0035] After sintering, component arrangement 17 can exhibit a shear strength of at least 20 MPa to about 150 MPa, such as at least about 40 MPa to about 100 MPa, such as at least about 60 MPa to about 80 MPa, as determined by a suitable shear tester. For example, shear strength can be measured using a Dage 4000 shear tester available from Nordson Dage in the UK. To measure shear strength, the displacement of shear movement is measured by the tester, and the corresponding shear strength is obtained up to the maximum shear force at shear fracture. The corresponding displacement value is recorded. For example, as used herein, shear strength refers to the magnitude of the force applied to peel the sintered component by pushing the first and second components in the lateral direction.

[0036] Furthermore, the metal powder used in the conductive paste can exhibit an ignition weight loss (e.g., Ig loss) of less than about 2% by weight, such as less than about 1% by weight, such as less than about 0.8%, such as less than about 0.5%. As used herein, “ignition weight loss” refers to the percentage by weight of metal powder lost from the conductive paste during material ignition. Ignition weight loss can be determined by calculating the weight of the sample before and after exposure to high temperatures. Ignition weight loss can be calculated by dividing the weight of the sample after ignition by the pre-ignition weight and multiplying by 100.

[0037] III. Methods

[0038] Figure 2 A flowchart depicts an example method for forming an article of articles (100) according to this disclosure.

[0039] At (102), the method includes disposing a conductive paste on a first component. The conductive paste may include a conductive material dispersed within an organic medium. The conductive paste may include the materials described above. In embodiments, the conductive material may include metal powder, such as silver. The organic medium may include polymers and solvents. The conductive paste may include about 1% to about 20% by weight of solvent and about 0.06% to about 0.5% by weight of polymer. The conductive paste may include about 70% to about 98% by weight of metal powder.

[0040] The conductive paste can be applied by any suitable method, such as screen printing and / or stencil printing. The conductive paste can have an application thickness of about 75µm to about 150µm, such as about 90µm to about 120µm, such as about 100µm to about 110µm, such as about 80µm to about 110µm.

[0041] At (104), the method includes drying the conductive paste prior to sintering. For example, the conductive paste may be dried in a furnace at a drying temperature for a desired amount of time. The drying temperature may range from about 80°C to about 200°C, such as from about 100°C to about 130°C, such as from about 110°C to about 140°C, such as from about 80°C to about 150°C. The drying time may also vary from about 5 minutes to about 20 minutes, such as from about 10 minutes to about 15 minutes. Drying may be carried out in any suitable furnace or heater.

[0042] After drying, the dried conductive paste may have a thickness ranging from about 20 µm to about 80 µm, such as from about 30 µm to about 70 µm, such as from about 40 µm to about 60 µm. Significantly, in embodiments, the thickness of the dried conductive paste may be reduced by at least about 25% and up to about 65%, such as about 50%, compared to the applied thickness.

[0043] At (106), the method includes placing a second component on a dry conductive paste. In such embodiments, a die may be used to bond a first component having a dry conductive paste thereon to a second component. For example, a first component having a dry metallic paste thereon may be disposed in the bottom of the die. The bottom of the die may have a temperature ranging from about 100°C to about 175°C. The second component may be disposed in the top of the die. The top of the die may have a temperature ranging from about 150°C to about 280°C. The first and second components may then be pressed together using the top and bottom of the die at a pressure of about 0.1 MPa to about 10 MPa (e.g., about 0.1 MPa to about 5 MPa) for a period of time of about 0.1 seconds to about 1 minute (e.g., about 1 second to about 20 seconds). The first component, the dry conductive paste, and the second component form a component arrangement, which may then be sintered.

[0044] At (108), the method includes sintering a component arrangement. The component arrangement may be sintered at a sintering temperature ranging from about 200°C to about 400°C (e.g., from about 250°C to about 350°C, or from about 250°C to about 300°C). The component arrangement may be sintered for a duration ranging from about 5 minutes to about 120 minutes, such as from about 15 minutes to about 90 minutes, or from about 30 minutes to about 60 minutes. Sintering of the component arrangement may be carried out in air or in an inert atmosphere containing an inert gas such as nitrogen. During sintering, the component arrangement may be sintered without applying any external pressure to it. For example, in an embodiment, the component arrangement may be sintered at a sintering pressure of about 0 MPa. In other words, as part of the sintering process, no external pressure needs to be applied to the component arrangement. Therefore, the component arrangement can be sintered in any furnace capable of reaching the desired sintering temperature. Advantageously, this method allows for a faster sintering process that does not require additional pressure during sintering. Therefore, such a method reduces processing time and cost. Furthermore, no additional solvent removal step is required during method (100).

[0045] The thickness of the sintered conductive paste disposed between the two components can be from about 20 µm to about 60 µm, such as from about 30 µm to about 50 µm. Significantly, in embodiments, the thickness of the sintered conductive paste can be reduced by at least about 10% and up to about 60%, such as about 20% and up to about 50%, compared to the thickness of the dried conductive paste.

[0046] Example

[0047] This disclosure is further illustrated by, but not limited to, the following embodiments.

[0048] An example conductive paste was prepared by dispersing various silver powders in a mixture of organic solvent and polymer. Dispersion was achieved by mixing the components in a mixer and then mixing them in a three-roll mill.

[0049] Examples and comparative examples of sintering in air are illustrated in Table 1 below. For example, Table 1 provides the D10, D50, and D90 of the metal powder used in each example, as well as the amounts of metal powder, solvent, and polymer. Representative die shear strengths for each example are also provided.

[0050] Table 1

[0051] An example paste stencil was printed onto the substrate surface using metal extrusion. The substrate was a copper substrate. Squares of conductive paste were printed onto the substrate, each measuring 13mm × 13mm. The squares had an applied thickness of 100µm. The squares were then dried at 120°C for 10 minutes. After drying, the thickness of the dried conductive paste squares was approximately 60µm. Chips were then mounted onto the dried conductive paste. Chips were mounted using a die bonder with bottom heating at 150°C and top heating at 175°C. The substrate with the dried conductive paste was mounted to the bottom of the die bonder, and the chip was mounted to the top. The die bonder pressed the substrate and chip together at a pressure of 1MPa for approximately 10 seconds. The substrate, dried conductive paste, and chip were then sintered in air at a sintering temperature of 290°C and a pressure of 0MPa for 30 minutes. There was no heating ramp. The sintered thickness of the paste was approximately 45µm.

[0052] After sintering and thermal cycling, the die shear strength between the chip and the copper plate for each embodiment was measured. Testing was performed using a bonding tester (4000 Plus, Nordson Advanced Technology Co., Ltd.) according to the standard die shear test method (MIL STD-883). Die shear strength was defined as the strength required to peel the copper chip through the bonding tester.

[0053] As depicted, representative embodiments of metal powders including those having a D50 ranging from about 210 nm to about 450 nm, a D10 ranging from about 150 nm to about 280 nm, and a D90 ranging from about 270 nm to about 930 nm provide suitable shear strengths ranging from about 22 mPa to about 83 mPa. Comparative examples, however, with D50 ranging from 1370 nm to 9130 nm, D10 ranging from 530 nm to 3180 nm, and D90 ranging from 2980 nm to 20,700 nm, exhibit unsuitable mPa values ​​ranging from 0.08 mPa to 0.64 mPa.

[0054] Examples and comparative examples of sintering in nitrogen are illustrated in Table 2 below. For example, Table 2 provides the D10, D50, and D90 of the metal powder used in each example, as well as the amounts of metal powder, solvent, and polymer. Representative die shear strengths for each example are also provided.

[0055] Table 2

[0056] An example paste template was printed onto the substrate surface using metal extrusion. The substrate was a silver substrate. Squares of conductive paste were printed onto the substrate, each measuring 13mm × 13mm. The squares had an applied thickness of 100µm. The squares were then dried at 120°C for 10 minutes. After drying, the thickness of the dried conductive paste squares was approximately 60µm. The chip was then mounted onto the dried conductive paste. The chip was mounted using a die bonder with bottom heating at 150°C and top heating at 175°C. The substrate with the dried conductive paste was mounted to the bottom of the die bonder, and the chip was mounted to the top of the die bonder. The die bonder pressed the substrate and chip together at a pressure of 1MPa for a period of approximately 10 seconds. The substrate, dried conductive paste, and chip were sintered in a nitrogen atmosphere, wherein nitrogen gas with a purity of >99.9995% by volume was introduced from a gas cylinder at a rate of 5 L / min for 3 minutes to purge air from the chamber prior to sintering, and was introduced at a rate of 2 L / min during sintering. Initially, sintering was initiated at 25°C with the heat ramped up at 0.5°C / s and held at 280°C for 30 minutes at 0 MPa, followed by cooling to 40°C at a rate of -1°C / s. The sintered paste thickness was approximately 45 µm.

[0057] After sintering and thermal cycling, the die shear strength between the chip and the silver plate for each embodiment was measured. Testing was performed using a bonding tester (4000 Plus, Nordson Advanced Technology Co., Ltd.) according to the standard die shear test method (MIL STD-883). Die shear strength was defined as the strength required to peel the copper chip through the bonding tester.

[0058] definition

[0059] As used herein, ranges and quantities can be expressed as “about” a specific value or range. “About” is intended to also include precise quantities. Thus, “about 5%” means “about 5%” as well as “5%”. “About” means within the typical experimental error expected for the intended application or purpose.

[0060] As used herein, “optional” or “optionally” means that the event or condition described below occurs or does not occur, and the description includes both the occurrence and non-occurrence of the event or condition. For example, an optional component in a method or composition means that the component may or may not be present in the method or composition.

[0061] As used herein, the term “substantially non-existent” means that there are trace amounts present in no more than negligible amounts and covers complete non-existence (e.g., 0 mol% to 0.01 mol%).

[0062] In this disclosure, common chemical abbreviations (such as those commonly found on the periodic table) are used to discuss chemical elements. For example, hydrogen is represented by its common chemical abbreviation H; helium by its common chemical abbreviation He; and so on.

[0063] Unless otherwise stated or explicitly implied by the context of the reference, all references to the singular feature or limitation of this disclosure shall include the corresponding plural feature or limitation, and vice versa.

[0064] The methods and compositions disclosed herein (including their components) may contain, consist of, or be substantially composed of the essential elements and limitations of the disclosure described herein.

[0065] These and other modifications and variations of this disclosure can be practiced by those skilled in the art without departing from the spirit and scope of this disclosure. Furthermore, it should be understood that aspects of the various embodiments are interchangeable in whole or in part. Moreover, those skilled in the art will understand that the foregoing description is merely illustrative and is not intended to limit the disclosure further described in the appended claims.

Claims

1. A sintering method for joining at least two components, the method comprising: A conductive paste is applied to the first component, the conductive paste comprising: Metal powder dispersed in an organic medium, the metal powder having a D50 in the range of about 200 nm to about 500 nm; The conductive paste is dried to form a dry conductive paste; The second component is disposed on the dried conductive paste to form a component arrangement; and The component arrangement is sintered without applying external pressure to it.

2. The method of claim 1, wherein drying the conductive paste comprises exposing the conductive paste to a drying temperature between about 80°C and 150°C for a period of about 1 minute to about 60 minutes.

3. The method of claim 1, wherein disposing the conductive paste on the first component comprises printing the conductive paste on the first component.

4. The method of claim 1, wherein placing the second component on the dried metal paste comprises placing the first component, having the dried metal paste on it, on the bottom of a die, the bottom of the die having a temperature ranging from about 125°C to about 200°C; placing the second component on the top of the die, the top of the die having a temperature ranging from about 150°C to about 225°C; and pressing the first component and the second component together under a pressure of about 0.1 MPa to about 10 MPa for a period of time ranging from about 0.1 seconds to about 20 seconds.

5. The method of claim 1, wherein sintering the component arrangement comprises exposing the component arrangement to a sintering temperature ranging from about 200°C to about 300°C for a sintering time of about 1 minute to 120 minutes.

6. The method of claim 1, wherein the component arrangement exhibits a shear strength of at least about 10 MPa to about 150 MPa.

7. The method of claim 1, wherein the particles in the metal powder comprise a coating.

8. The method of claim 7, wherein the coating comprises one or more lipids.

9. The method of claim 8, wherein the one or more lipids comprise one or more fatty acids.

10. The method of claim 1, wherein the metal powder comprises D90 of about 250 nm to about 930 nm.

11. The method of claim 1, wherein the metal powder comprises D10 of about 150 nm to about 300 nm.

12. The method of claim 1, wherein the metal powder comprises silver.

13. The method of claim 1, wherein at least 60% of the metal powder comprises spherical particles.

14. The method of claim 1, wherein after sintering, the metal powder has an Ig- loss of about 0.5% to about 0.75%.

15. The method of claim 1, wherein after sintering, the conductive paste forms rounded corners on the sidewalls of the chip, wherein the rounded corners have a height of less than about 30 µm.

16. The method of claim 1, wherein the organic mediator comprises a solvent and a polymer.

17. The method of claim 15, wherein the conductive paste comprises about 1% by weight to about 20% by weight of a solvent.

18. The method of claim 15, wherein the conductive paste comprises about 0.6% by weight to about 1% by weight of the polymer.

19. The method of claim 1, wherein the conductive paste comprises about 70% by weight to about 98% by weight of conductive material.

20. An electronic article comprising a semiconductor chip sintered to a substrate with a conductive paste, the conductive paste comprising metal powder dispersed in an organic medium, the metal powder having a D50 in the range of about 200 nm to about 500 nm.